1992
DOI: 10.1034/j.1600-0889.1992.t01-1-00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Saharan dust in the Amazon Basin

Abstract: Saharan dust is shown to enter the Central Amazon Basin (CAB) in bursts which accompany major wet season rain systems. Low‐level horizontal convergence feeding these rain systems draws dust from plumes which have crossed the tropical Atlantic under the large‐scale circulation fields. Mass exchange of air between the surface and 4 km over the eastern Amazon basin is calculated using rawinsonde data collected during storm events. Mean concentrations of dust observed by aircraft over the western tropical Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
382
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(410 citation statements)
references
References 0 publications
12
382
0
2
Order By: Relevance
“…The frequent intrusion of LRT aerosols is a characteristic feature during the Amazonian wet season and represents a strong and important impact on the Amazonian ecosystem (e.g., Chen et al, 2009;Bristow et al, 2010;Baars et al, 2011;Abouchami et al, 2013;Yu et al, 2015;Rizzolo et al, 2016). These LRT plumes mostly comprise a complex mixture of Saharan dust, African 10 biomass burning smoke, and marine aerosols from the transatlantic air passage (e.g., Talbot et al, 1990;Swap et al, 1992;Glaser et al, 2015).…”
Section: Aerosol and Ccn Time Series For Representative Wet Season Comentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent intrusion of LRT aerosols is a characteristic feature during the Amazonian wet season and represents a strong and important impact on the Amazonian ecosystem (e.g., Chen et al, 2009;Bristow et al, 2010;Baars et al, 2011;Abouchami et al, 2013;Yu et al, 2015;Rizzolo et al, 2016). These LRT plumes mostly comprise a complex mixture of Saharan dust, African 10 biomass burning smoke, and marine aerosols from the transatlantic air passage (e.g., Talbot et al, 1990;Swap et al, 1992;Glaser et al, 2015).…”
Section: Aerosol and Ccn Time Series For Representative Wet Season Comentioning
confidence: 99%
“…The African continent is of significant importance for the Amazonian atmospheric composition as it represents a major source of desert dust and pollution aerosols (e.g., Swap et al, 1992;Andreae et al, 1994;Yu et al, 2015;Rizzolo et al, 2016). A systematic overview of the properties and relevance of LRT plume arrival in the ATTO region during the Amazonian wet season can be found in Moran-Zuloaga et al (2017).…”
mentioning
confidence: 99%
“…Furthermore Dadkhah & Griffiths (2005) reported a significant effect of such atmospheric suspended dust particle on the growth of wheat plant. Similarly, Swap et al (1992) and Koren et al (2006) reported a significant effect of desert soil on the fresh & dry weight and height of plants. Productivity of Amazon basin and efficiency of its rainforests is owing to transport, 40 million tons of dust every year (Emdad & Fardad, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Deposition of atmospheric dust, usually defined in the aeolian literature as a suspension of solid particles in the atmosphere with a grain size inferior to about 100 mm [Pye, 1987], has been identified as an important environmental process [Swap et al, 1992;Shinn et al, 2000]. Various theoretical and practical techniques to calculate or measure the dry aeolian deposition of dust on a surface have been proposed (for reviews, see Seinfeld and Pandis [1998], Etyemezian et al [2003], and Goossens [2005]).…”
Section: Introductionmentioning
confidence: 99%